Water and nutrient availability modulate the salinity stress response in Olea europaea cv. Arbequina - Marzia Vergine; Emily Rose Palm; Anna Maria Salzano; Carmine Negro; Werther Guidi Nissim; Leonardo Sabbatini; Raffaella Balestrini; Maria Concetta de Pinto; Nunzio Dipierro; Gholamreza Gohari; Vasileios Fotopoulos; Stefano Mancuso; et al. (Plant Stress, 2024)
Salinity stress represents a key factor for global agriculture. Plants can respond to salinity stress by adapting their physiology in different ways with the aim of limiting reductions in growth and development. Importantly, moisture retention capacity, permeability and nutrient availability of substrates represent critical variables for plants as they may further influence the effect of osmotic stress. Here, a multidisciplinary approach was applied to evaluate the role of two different substrates, peat and perlite, on 2-year-old potted cuttings of Olea europaea (cultivar Arbequina) under different salinity stress conditions (0, 100 and 200 mM NaCl). Biometric and physiological data indicate that plants potted in perlite (AP) generally present lower growth and photosynthetic rates when compared with peat (AS) in combination with salinity stress. Ion measurements indicate a rise in Na+ accumulation with increasing stress severity, which alters the ion ratio in both substrates. In addition, differences occurred in polyphenol contents, with a general increase in quinic acid and rutin contents in AS and AP samples, respectively. Metabolomic and biometric data were also coupled with metabarcoding analysis, which indicates that the moderate salinity treatment (100 mM NaCl, T100) reshaped the endophytic community of plants grown on both substrates. Taken together, the data suggest that the strategy used by a glycophytic species such as the olive tree to cope with salinity stress seems to be highly related to availability of water and nutrients. The lack of both may be simulated by perlite, enhancing the effect of salinity stress response in woody plants. Lastly, applying the beneficial endophytic bacterial taxa identified here could represent a step forward in increasing plant defence and nutrient uptake and reducing inputs for modern and more sustainable agriculture.